(untitled) (International Association of Biologicals and Computational Digest, 2022)
Cancer i s a group of abn ormal cells. The unregulated gro wth factor recepto r t yrosin e kinase ( GFR- TK) proteins are implicated in the proliferation o f mo re than 60 % o f all can cer t ypes. Screenin g o f ph ytoch emicals for their anti - angiogenic potential has b een a gro wing area o f research in the mod ern d ecad e. There i s a well - kno wn principle that natural co mpounds are active against several diseases, includin g variou s t yp es of can cer. Th e present research work fo cuses on kno wn gro wth factor receptors ( GFRs) as an important target fo r co mputation al s tudies. In this stud y, 96 curated anti - can cer co mpounds were virtu ally screened against the EGFR, FGFR, IGFR, and HGFR usin g molecular dockin g so ftware. For each GFR, we h ave considered ten top most results as potential hits. Among them, co mmon f i ve results are: Spiro solan e, Ginkgetin, Fangchinoline, Theaflavin and Ursolic acid. These co mpounds have b een reported to show antican cer activities in the l i t erature. With the help of different interaction analysis tools, the protein - l i gand inter action patterns between th e functional groups o f these co mpounds were analyzed. Hydro gen bonding and h ydrophobic forces are th e main co mponents o f th e interactions o f th ese hits, similar to those exp erimental fo r th e kno wn inhibitors. Fro m the maximu m nu mb ers o f hits, i t could be indicated that co mpounds Spirosolan e, Ginkgetin, Fan gchinoline, Th eaflavin and Ursolic acid are pro miscuous l ead s in the drug disco very process.